Metallothioneins in Inflammatory Bowel Diseases: Importance in Pathogenesis and Potential Therapy Target. (26th April 2021) - Socha-Banasiak, Anna; Sputa-Grzegrzółka, Patrycja; Grzegrzółka, Jędrzej; Pacześ, Krzysztof; Dzięgiel, Piotr; Sordyl, Beata; Romanowicz, Hanna; Czkwianianc, Elżbieta
Abstract : Immunological disorders, increased oxidative stress, and damage to the epithelial barrier play an important role in the pathogenesis of inflammatory bowel diseases (IBDs). In the treatment of patients with Crohn's disease (CD) and ulcerative colitis (UC), it is increasingly common to use biological drugs that selectively affect individual components of the inflammatory cascade. However, administering the medicines currently available does not always result in obtaining and maintaining remission, and it may also lead to the development of resistance to a given agent over time. Metallothioneins (MTs) belong to the group of low molecular weight proteins, which, among others, regulate the inflammation and homeostasis of heavy metals as well as participating in the regulation of the intensity of oxidative stress. The results of the studies conducted so far do not clearly indicate the role of MTs in the process of inflammation in patients with IBD. However, there are reports that suggest the possibility of using MTs as a potential target in the treatment of this group of patients.